Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) Ta có:
\(\left(a+b\right)\left(a+c\right)+\left(c+a\right)\left(c+b\right)\)
\(=a^2+ac+ab+bc+c^2+bc+ac+ab\)
\(=a^2+c^2+2ac+2bc+2ab\)
Thay \(a^2+c^2=2b^2\) vào biểu thức ta được:
\(=2b^2+2ac+2bc+2ab\)
\(=2\left(b^2+ac+bc+ab\right)\)
\(=2\left[\left(b^2+bc\right)+\left(ac+ab\right)\right]\)
\(=2\left[b\left(b+c\right)+a\left(c+b\right)\right]\)
\(=2\left(b+a\right)\left(b+c\right)\)
\(\RightarrowĐpcm\)
\(a,\left(a+b\right)\left(a^2-ab+b^2\right)+\left(a-b\right)\left(a^2+ab+b^2\right)\)\(=\left(a^3+b^3\right)+\left(a^3-b^3\right)=2a^3\Rightarrowđpcm\)
\(b,\left(a+b\right)\left[\left(a-b\right)^2+ab\right]=\left(a+b\right)\left(a^2-2ab+b^2+ab\right)=\left(a+b\right)\left(a^2-ab+b^2\right)\)\(=\left(a^3+b^3\right)\Rightarrowđpcm\)
\(c,\left(a^2+b^2\right)\left(c^2+d^2\right)=a^2c^2+a^2d^2+b^2c^2+b^2d^2=\left(a^2c^2+2abcd+b^2d^2\right)+\left(a^2d^2-2abcd+b^2c^2\right)\)\(=\left(ac+bd\right)^2+\left(ad-bc\right)^2\Rightarrowđpcm\)
a) (a+b)(a2-ab+b2)+(a-b)(a2+ab+b2)
= a3+b3+a3-b3 = 2a3
b) a3+b3
= (a+b)(a2-ab+b2)
= (a+b)(a2- 2ab+b2)+ab
= (a+b)(a2-b2)+ab
a) \(\left(a+b\right)\left(a^2-ab+b^2\right)+\left(a-b\right)\left(a^2+ab+b^2\right)\)
=\(a^3+b^3+\left(a^3-b^3\right)\)
=\(a^3+b^3+a^3-b^3\)
=\(2a^3\)
b) \(a^3+b^3=\left(a+b\right)\left(a^2-ab+b^2\right)\)
=\(\left(a+b\right)\left(a^2-2ab+b^2-ab\right)\)
=\(\left(a+b\right)\left[\left(a^2-2ab+b^2\right)-ab\right]\)
=\(\left(a+b\right)\left[\left(a-b\right)^2-ab\right]\)
a. \(\left(a+b\right)\left(a^2-ab+b^2\right)+\left(a-b\right)\left(a^2+ab+b^2\right)=a^3+b^3+a^3-b^3=2a^3\)
b. \(a^3+b^3=\left(a+b\right)\left(a^2-ab+b^2\right)=\left(a+b\right)\left(a^2-2ab+b^2+ab\right)=\left(a+b\right)\left[\left(a-b\right)^2+ab\right]\)
a)\((\dfrac{5}{7}x^2y)^3:(\dfrac{1}{7}xy)^3\)
=\((\dfrac{5}{7}x^2y:\dfrac{1}{7}:x:y)^3\)
=(\(\dfrac{5}{7}.7.x^2:x.y:y)^3\)
=(5x)\(^3\)
=5\(^3\).x\(^3\)
=125.x\(^3\)